2019
DOI: 10.5152/turkjorthod.2019.18043
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Pain, Anxiety, and Cortisol Levels During the Initial Aligning Phase of Fixed Orthodontic Treatment

Abstract: Turkish Journal of Orthodontics (Turk J Orthod) is an international, scientific, open access periodical published in accordance with independent, unbiased, and double-blinded peer-review principles. The journal is the official publication of Turkish Orthodontic Society and it is published quarterly on March, June, September and December. Turkish Journal of Orthodontics publishes clinical and experimental studies on on all aspects of orthodontics including craniofacial development and growth, reviews on current… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 24 publications
1
12
1
Order By: Relevance
“…Caution is suggested when comparing the actual findings with others, since there are methodological limitations as the lack of information on the patients’ age, mechanics applied and magnitude of malocclusion, which can compromise the results 7,9,13 . Additionally, only one study 12 considered anxiety in the exclusion criteria, which can influence the pain perception 19 and should not be neglected in pain perception studies. According to a systematic review, 14 only one study that investigated the pain perception with aligners and conventional appliances was considered to have a high level of evidence 12 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Caution is suggested when comparing the actual findings with others, since there are methodological limitations as the lack of information on the patients’ age, mechanics applied and magnitude of malocclusion, which can compromise the results 7,9,13 . Additionally, only one study 12 considered anxiety in the exclusion criteria, which can influence the pain perception 19 and should not be neglected in pain perception studies. According to a systematic review, 14 only one study that investigated the pain perception with aligners and conventional appliances was considered to have a high level of evidence 12 .…”
Section: Discussionmentioning
confidence: 99%
“…Although there are controversies regarding these factors on the pain process, we still decided to match them to ensure similar extents of tooth movement in both groups. 3 Other behavioural factors as the degree of pain vigilance, 16,17 anxiety 18,19 and catastrophizing 20,21 or the pain modulation profile 15 can potentiate the pain, increasing the perception and decreasing the tolerance. For this reason, we also aimed to understand more thoroughly the participation of these factors in determining the pain levels in order to eliminate all biases that could influence the pain response.…”
Section: Ta B L Ementioning
confidence: 99%
See 1 more Smart Citation
“…Most of the published studies that quantify pain and the impact of treatment on OHRQoL have used brackets with a 0.022" slot [19,20,22,23], with only a few studies using brackets with a 0.018" slot [27]; hence the justification for analyzing the influence of slot size in this study. El-Angbawi AM et al analyzed the influence of slot size (0.018" with 0.022") on pain during orthodontic treatment, and concluded that there were no statistically significant differences between the two study groups.…”
Section: Discussionmentioning
confidence: 99%
“…Fear of pain may prevent patients from undergoing orthodontic treatment, and painful experiences may lead to discontinuing their treatment [ 5 ]. Pain and discomfort have been evaluated during different orthodontic procedures from the first stages of elastomeric separators [ 6 , 7 ] through archwire replacements [ 8 ] and till the end of treatment and retainers wear [ 9 ]. The intensity of the pain associated with orthodontics increases with the increase in the duration of treatment [ 10 ].…”
Section: Introductionmentioning
confidence: 99%